Experience of morning reports in the emergency department. Issue 7 (July 2015) - Sabbagh, C.; Chaddad, M.; El Rassy, E.
Abstract Morning report in the emergency medicine departments is an emerging teaching modality in the medicine curriculum. Our institution, Hotel‐Dieu de France hospital, a multidisciplinary tertiary care university hospital affiliated to the Saint Joseph University of Medical Sciences, is the only hospital in Middle East to hold morning reports in the emergency department (ED). We evaluate the usefulness of the morning report as a pedagogic tool as it assesses the content, quality of the discussions, professionalism, leadership, participation and duration of the morning report. The particularity of this paper is that it takes into consideration the interns' input often under‐recognised in the studies. An anonymous questionnaire was diffused to the residents and interns that rotated in the ED during the previous year. It consisted of seven multiple‐choice questions to evaluate the quality of the presentations, targeted discussions, ethics and professionalism, evidence‐based medicine, clinical reasoning, relation of cases to discussions and implication of the ED physician. Overall, of the 63 patients who answered the survey, 65.1% were satisfied by the content. The majority considered the quality of the discussions acceptable and the leadership and participation satisfactory, professionalism was judged poor. Both residents and interns were satisfied of the teaching point of the morning reports. The only fail back observed was professionalism and pathophysiological discussions that require to be added to the sessions, whereas clinical management, teaching points, leadership and time management were completely satisfactory.